Tests on a scale for measuring the core competencies of paediatric specialist nurses: An exploratory quantitative study - Qian Tang; Dahua Zhang; Jianjun Chen; Meihua Liu; Yuqiong Xiang; Tingwei Luo; Lihui Zhu (Wiley, 2023)
Abstract Aim This study aimed to develop a tool to measure paediatric specialist nurses' core competencies and examine the scale's validity and reliability. Design An exploratory quantitative study. Methods This study was performed in April 2022 with 302 paediatric specialist nurses in mainland China. Items were created through a literature review, a qualitative interview, and the Delphi method. The data were evaluated using descriptive statistics, independent sample t‐test, explanatory factor analysis, Pearson correlation coefficient, Cronbach's alpha coefficient and split‐half reliability. Results The final scale consisted of five factors and 32 items. The factors were communication, coordination and judgement abilities; professional technology mastery ability; specialist knowledge mastery ability; medical‐related processes; and evidence‐based nursing competencies. The explained total variance of the five factors was 62.216%. The scale‐level and item‐level CVI of this scale was 1.00, and the mean CVR of the total scale was 0.788. The Pearson correlation coefficients of each dimension and the total dimension of the scale was 0.709-0.892, and within each dimension, it was 0.435-0.651. The Cronbach's α of this scale was 0.944, and its split‐half reliability was 0.883.